The Concept of the Caliph for the Development of Student Leadership Character for the SDGS Perspective of Tafsir Tarbawi - Achmad Ghiyats Setiawan; Cucu Surahman; Elan Sumarna (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to examine the concept of the caliph in the Qur'an from the perspective of tarbawi interpretation as the basis for developing student leadership character to support the achievement of the Sustainable Development Goals (SDGs), especially in the pillars of quality education (SDG 4), peace and justice (SDG 16), and partnerships to achieve goals (SDG 17). Theoretical framework: Theoretically, this research is based on the tarbawi interpretation approach, which is the interpretation of Qur'anic verses that emphasizes the values of education and character formation. Literature review: The literature studied includes classic and contemporary tafsir books such as Tafsir al-Misbah, and Tafsir Ibn Kathir, as well as scientific studies related to Islamic character education and leadership in the context of education. Methods: The research method used is qualitative through library research. The data collection technique is carried out by studying the text and analyzing the content of the verses of the Qur'an, especially QS. Al-Baqarah: 30 and QS. Shad: 26, as well as the interpretation of the scholars of these verses. Results: The results of the study show that the concept of the caliphate reflects the role of humans as leaders who are responsible for maintaining justice, and trust, and fostering a generation that obeys divine and humanitarian values. These leadership values are in line with the principles of character education that are needed in the formation of young leaders with integrity, vision, and sustainability. Implications: The implication of this study is the need to integrate the concept of the caliphate in the curriculum of character education of students in schools, both formal and informal, to instill Islamic leadership values from an early age. Novelty: The novelty of this research lies in the affirmation of the interpretation of tarbawi as a strategic approach in bridging Islamic teachings and the global goals of the SDGs, as well as as a holistic and transformative model of leadership character education.